The Chronology of Augustine’s Sermones ad populum III: On Christmas Day - Drobner, Hubertus R. (Augustinian studies, 2004)
This article continues the discussion of dating Augustine’s sermons, using Augustine’s Christmas sermons (184-196 and 369-370) as the basis. It also includes an excursus, summarizing the status of present discussions and identifying the value and goal of this effort from a methodological perspective.